Random Forest for Multitemporal and Multiscale Classification of Remote Sensing Satellite Imagery - Chitradevi, A; Vijayalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
An increasing number of optical High-Resolution (HR) remote sensing satellite systems, offering multispectral images. However, acquiring multi temporal HR data may not always be economically viable, particularly for large areas. Data having medium resolution (i.e., a GSD of 30 m) do not offer as much detail, but cover a larger area and may often be preferable from an economical point of view. In this research work present a new method for the multi temporal and contextual classification of georeferenced optical remote sensing images acquired at different epochs with having different geometrical resolutions. The method is based on Conditional Random Fields (CRFs) for contextual classification. But in CRF, pool of features used in this work is rather limited, particularly for the medium-resolution images. To solve this problem proposed work is expanded to pool of features for the medium-resolution images to improve the classification results. The Gaussian model used in the CRF is should be replaced by more sophisticated Random Forests (RFs) classifiers. RF is an ensemble of many decision trees, which have been trained on randomly selected pool of features for the medium-resolution images subsets of the training data, in order to decorrelate the individual trees. Extend such a framework to multitemporal classification and change detection, taking into account interactions between images acquired at different epochs and considering the fact that these images may have different geometrical resolutions. Results are given for two different test sites in Germany, where Ikonos, RapidEye, and Landsat images are available. State-of-the-art multitemporal classification method and that it is feasible to detect changes in lower resolution images.